The Value of High-Frequency Repetitive Transcranial Magnetic Stimulation of the Motor Cortex to Treat Central Pain Sensitization Associated With Knee Osteoarthritis - Nguyen, Jean-Paul; Dixneuf, Véronique; Esnaut, Julien; Moreno, Alcira Suarez; Malineau, Catherine; Nizard, Julien; Lefaucheur, Jean-Pascal (Frontiers in Neuroscience, 2019)
Aim: Chronic pain associated with knee osteoarthritis may develop in connection with a maladaptive process of pain sensitization in the central nervous system. Repetitive transcranial magnetic stimulation (rTMS) has been proposed to treat various pain syndromes related to central sensitization phenomenon, but was never applied in the context of knee osteoarthritis. Methods: A 71-year-old woman presenting clinical evidence of central sensitization of pain associated with left knee osteoarthritis underwent monthly sessions of rTMS delivered at 10 Hz over the right motor cortex. Results: From the week following the 3rd session, she began to improve on various clinical aspects, including pain. After 10 sessions (i.e. almost one year of follow-up), pain was reduced by 67%, especially regarding neuropathic components, while sleep disorders and fatigue also improved by 57-67%. The Central Sensitization Inventory score was reduced by 70% Conclusion: This observation suggests that high-frequency motor cortex rTMS could be a therapeutic option to treat neuropathic pain and psychological symptoms associated with central sensitization developing in the context of chronic osteoarthritis of the knee joint.